ROLE OF EXTRALINGUISTIC FACTORS IN THE FORMATION OF LANGUAGE PERSONALITY OF BILINGUAL CHILD - Kytina, V.V. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
This article describes the influence of extralinguistic factors on the formation of linguistic identity of bilingual child. The problem of multilingualism is determined by extralinguistic factors, indicating that modern society and the processes occurring in it are forcing people to change their lives, and with it language. The relevance of the study determined that polylingual in the world than monolingual. And the children’s bilingualism is characteristic for half of the population on our planet. The phenomenon of multilingualism is not a given, and the need for continued development taken first by parents and caregivers, the teachers, and then by the children. We do not choose if the child will be bilingual, and he forced to become bilingual due to differences in family language, environment, and relation to a specific life situation. A bilingual child is a member of several societies, more ethnosociology (because the society that surrounds the baby carrier one national picture of the world, and the family is the bearer of another national pic-ture of the world). It is the tandem of parents and teachers is a point of support for the polylingual child. In this process, form a view about the world around himself and about the features of every ethnic group and about his belonging them. We can assume that we are talking about the formation of such concepts as “man of peace”.